Acinic cell carcinoma of the parotid gland. Case report - Dąbrowski, Jarosław; Piętka, Tomasz; Przybysz, Jan; Krzymański, Grzegorz (Contemporary Oncology/Współczesna Onkologia, 2011)
The authors highlight a rare type of parotid gland tumour, presenting past and contemporary treatment options for this entity, and underscore the necessity of therapy individualization in every single case. Acinic cell carcinoma (ACC) is a rare salivary gland tumour accounting for 6 to 15% of all malignant neoplasms of the parotid gland. Although ACC belongs to low-grade malignant tumours, there can be seen ones with aggressive behaviour, rapid progression and a tendency to metastasize. We present a case of a locally advanced ACC without clinically detectable metastases. Diagnostic imaging (MRI and USG) and a surgical biopsy were performed to establish the diagnosis and assess the extent of this huge tumour. The patient was qualified for surgery (total parotidectomy with MRND III). The postoperative period was complicated by partial necrosis of the skin flap used to close the pre-auricular area defect. There was no postoperative radiotherapy because of the lack of nodal involvement and the prolonged wound healing. After 24 months of postoperative follow-up there is no evidence of recurrence of the tumour.